Dr. Hui Li—thoracic surgeon in Beijing Chao-Yang Hospital: a good doctor is a master of his scalpel and his thoughts - Liao, Lili (Journal of Thoracic Disease; Vol 9, No 7 (July 31, 2017): Journal of Thoracic Disease, 2017)
The higher we are, the further we see. From a different angle, we may view the world in a different way. Sometimes, we are unaware that a tiny event can influence a person so deeply that his life would be changed due to it; and that a “big discovery” might in fact have been long known to counterparts in the field. No matter who you ask, a friend, a tutor, a colleague, or a student, they will ask you something they have always wondered. It seems as though we live in a world with a vastness of unknowns and it is a fascinating process to discover them by seeing things from different angles.